2022
DOI: 10.1002/aenm.202200493
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Advances on Single Atom and Atomic Cluster‐Decorated Low‐Dimensional Platforms towards Superior Electrocatalysts

Abstract: The fundamental relationship between structure and properties, which is called “structure‐property”, plays a vital role in the rational designing of high‐performance catalysts for diverse electrocatalytic applications. Low‐dimensional (LD) nanomaterials, including 0D, 1D, 2D materials, combined with low‐nuclearity metal atoms, ranging from single atoms to subnanometer clusters, are currently emerging as rising star nanoarchitectures for heterogeneous catalysis due to their well‐defined active sites and unbeata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 217 publications
0
23
0
Order By: Relevance
“…Compared with isolated atoms or sub-NPs, the MNCs tend to endow more satisfactory activity and selectivity for HER, attributing to their quantum size effect, surface geometric effect, and unique electronic properties. [35,36] Especially, the atomic level catalytic sites with abundant unsaturated and low coordination atoms are proved to be active centers in catalytic reactions (Figure 1). However, the MNCs tend to aggregate during the preparation owing to the high surface energy, which is a challenge in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with isolated atoms or sub-NPs, the MNCs tend to endow more satisfactory activity and selectivity for HER, attributing to their quantum size effect, surface geometric effect, and unique electronic properties. [35,36] Especially, the atomic level catalytic sites with abundant unsaturated and low coordination atoms are proved to be active centers in catalytic reactions (Figure 1). However, the MNCs tend to aggregate during the preparation owing to the high surface energy, which is a challenge in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is important considering the nanoscale-enhanced atomic diffusion, surface mobility, and surface interaction energies that contribute significantly to the low-temperature surface-mediated sintering of the nanoparticles or dispersion into clusters or single atoms. [282][283][284][285] Future development of the in situ/operando TEM and combined techniques will continue to play an increasingly important role not only in controlling or improving the existing catalysts for the various catalytic reactions, but also in designing or preparing new catalysts for advancing the cutting-edge areas of sustainable energy research and applications.…”
Section: Discussionmentioning
confidence: 99%
“…The ONi 2 N 6 , Ni 2 N 6 , and NiN 4 structural models were constructed, respectively, and DFT calculations were performed. [ 40,145 ] The results showed that the ONi 2 N 6 structure participated in the reaction and the free energy for the generation of COOH* intermediate by activating CO 2 was significantly lower than that of the Ni 2 N 6 and NiN 4 structures. At the same time, compared with Ni 2 N 6 and NiN 4 , ONi 2 N 6 structure had the weakest adsorption capacity for CO, and the generated CO* intermediate was more easily desorbed to generate CO.…”
Section: Preparation Strategy Of Diatomic Catalystmentioning
confidence: 99%
“…The ONi 2 N 6 , Ni 2 N 6 , and NiN 4 structural models were constructed, respectively, and DFT calculations were performed. [40,145] The results showed Small 2022, 18, 2203589 (a-g) Reproduced with permission. [135] Copyright 2022, Elsevier.…”
Section: Strategy Of Metal Cluster Precursorsmentioning
confidence: 99%